CUSTOMER PREFERENCE ANALYSIS ON ATTRIBUTES OF HYBRID ELECTRIC VEHICLE: A CHOICE-BASED CONJOINT APPROACH - Vinstein Silaen, Randy
Adoption of electric vehicles (EV) and the development of supporting infrastructure is one of the primary government measures to eliminate this dependency on internal combustion engines (ICE) and substantially reduce carbon dioxide (CO2) emissions from the transportation sector. EV will lessen the nation's reliance on imported crude oil, improve the trade balance and national energy security, and reduce the cost of fossil fuel subsidies to the state budget. In accordance with Presidential Regulation No. 55 of 2019 addressing the acceleration of the Battery-Based Electric Motor Vehicle (KBLBB) program for highway mobility, the Indonesian Ministry of Industry has set a 20% target for the use of electric battery-powered vehicles by 2025. In addition to providing incentives and charging infrastructure for electric vehicles, the KBLBB program also regulates electricity rates, technical requirements, and ultimately environmental preservation. The government hopes the growth of the environmentally friendly automotive industry in this area would support the carbon emission reduction target. Thus, the transportation industry may lead a transition by developing electric vehicles and a green ecosystem.